Education of the child with epilepsy as the element of its wellness’ improvement - Dubelt, Joanna; Cybula-Misiurek, Małgorzata; Czerwińska Pawluk, Iwona; Chrościńska–Krawczyk, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2018)
Epilepsy is the most common disease of the nervous system. Its etiology is multifactorial. The greatest risk for the occurrence of this disease is observed in children in the first decade of their life. The diagnosis of epilepsy and problems related to it affect not only the child but the whole family. It is important to take comprehensive measures of prevention and education to ensure patient safety and allow them to lead a normal life.